A Compilation of Evaristo Arineitwe’s Published Poetry - Arineitwe, Evaristo (International Human Rights Arts Movements, 2024)
Abstract The following poems have been written by Arineitwe Evaristo, an upcoming poet from Kabale District, Western Uganda. His first poem is titled “The Return” and was published in an anthology titled Where Broken Hearts Go and Other Poems edited by Egara Kabagi (Etal). Other three poems; “Loud Silence”, “The War Mongers” and “Boiling Point” have been published in Thorns Tears and Treachery, a Collection of Poems, Essays and Artwork on the Sudanese Civil War by The International Human Rights Arts Movement (IHRAM). This poetry writing is basically informed by the political dilemma that grips the African continent after independence (Neo-colonialism), nostalgia or/and reminiscence, the devastating effects of climate change and life in general. Tentatively titled The Last Flicker is yet another collection of poetry that is yet to be published.